Brain morphometry of preschool age children affected by autism spectrum disorder: Correlation with clinical findings. Issue 1 (26th December 2018) - Lucibello, S.; Verdolotti, T.; Giordano, F. M.; Lapenta, L.; Infante, A.; Piludu, F.; Tartaglione, T.; Chieffo, D.; Colosimo, C.; Mercuri, E.; Battini, R.
Abstract : The aim of our study was to use a combined imaging and clinical approach to identify possible patterns of clinical and imaging findings in a cohort of preschool age autism spectrum disorder (ASD) patients. In order to identify imaging patterns that could be related to specific clinical features, a selected group of ASD patients (age range 3–6 years) without dysmorphic features, epilepsy or other major neurological signs, malformations or other lesions at MRI was subjected to brain volumetric analysis using semiautomatic brain segmentation. An age‐matched group of typically developing children was subjected to the same analysis. Our results were consistent with previous literature: Total gray matter volume, total cortical gray matter volume and amygdalar volumes were significantly greater in the ASD group than the control group. When we divided the study group into subgroups on the basis of clinical findings such as high‐ or low‐functioning, or verbal and nonverbal, the only significant difference between verbal and nonverbal subjects was in cerebellar hemispheric size. In conclusions, our results confirm that newer brain MRI techniques using semiautomatic brain segmentation can provide information useful for defining the differences between ASD patients and controls, particularly if they form part of an integrated approach between MRI and cognitive‐behavioral and genetic data. Clin. Anat. 32:143–150, 2019. © 2018 Wiley Periodicals, Inc. Highlights: Combined imaging and clinical approach in autism spectrum disorders Semiautomatic brain segmentation in a selected preschool age ASD group Reduced total cerebellar white matter volume in non‐verbal ASD patients